1999
DOI: 10.1093/jn/129.5.1010
|View full text |Cite
|
Sign up to set email alerts
|

Select 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitors Vary in Their Ability to Reduce Egg Yolk Cholesterol Levels in Laying Hens through Alteration of Hepatic Cholesterol Biosynthesis and Plasma VLDL Composition

Abstract: The inability to markedly attenuate cholesterol levels in chicken eggs has led to speculation that cholesterol is essential for yolk formation and that egg production would cease when yolk cholesterol deposition was inadequate for embryonic survival. However, this critical level hypothesis remains unproven. Here, we determine the relative responsiveness of laying hens to three select inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR), the rate-limiting enzyme of cholesterol biosynthesis. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 57 publications
3
28
0
1
Order By: Relevance
“…Apparently, reducing serum cholesterol concentration was consistently followed by decreasing of egg cholesterol content Liver and ovary are the primary organ of cholesterol synthesis in laying hen. However, there is little, if any, direct transfer of ovariansynthesized cholesterol to develop oocyte (Elkin et al,1999). Thus, the contribution of the ovaries on egg cholesterol levels are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, reducing serum cholesterol concentration was consistently followed by decreasing of egg cholesterol content Liver and ovary are the primary organ of cholesterol synthesis in laying hen. However, there is little, if any, direct transfer of ovariansynthesized cholesterol to develop oocyte (Elkin et al,1999). Thus, the contribution of the ovaries on egg cholesterol levels are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the value of t 1/2kel obtained in turkey was also lower compared to the data from humans or pigs, but the differences were not so large as compared to the differences in C max . In a previous study reduction of cholesterol level in eggs was observed in laying hens treated with SIM at a daily dosage of 60 mg/hen (Elkin et al 1999). The obtained results suggest that for effective reduction of cholesterol level in products of poultry origin much more higher doses of SIM should be used compared to those used in humans.…”
Section: Parametermentioning
confidence: 65%
“…The HMG-CoA reductase inhibitors (also called statins) are known to decrease plasma cholesterol by inhibition of cholesterol biosynthesis. Elkin et al (1999) showed that SIM reduced egg cholesterol contents in laying hens as well as liver and plasma cholesterol concentrations. Due to the significant contribution of cholesterol in the pathogenesis of atherosclerosis and Correspondence to: J. Jaroszewski, e-mail: jerzyj@uwm.edu.pl, tel.…”
Section: Introductionmentioning
confidence: 98%
“…Eggs were collected as described above, weighed, and the yolks were separated as described previously (Elkin et al, 1999). Each yolk was then transferred to an individual 150-mL polypropylene sample cup, stirred to homogeneity with a spatula, and lyophilized.…”
Section: Analytical Methodologiesmentioning
confidence: 99%